2012
DOI: 10.1016/s1413-8670(12)70319-7
|View full text |Cite
|
Sign up to set email alerts
|

YMDD motif mutations in chronic hepatitis B antiviral treatment naïve patients: a multi-center study

Abstract: Mutation of YMDD motif was detectable at a high rate in CHB patients in this study. The incidence of YMDD may be correlated with HBeAg and HBV DNA level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
1
18
2
1
Order By: Relevance
“…No mutation was noted in 33.2% of the cases. It was reported that the infection rates of mutant virus in antiviral treatment naïve patients could be influenced by the mutant virus prevalence in the society [7, 8]. Where there is no available data for HBV mutation rates, the mutation rates in the chronic HBV patients visiting hospital might be utilized to postulate the infection rates of mutant virus in antiviral treatment naïve patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No mutation was noted in 33.2% of the cases. It was reported that the infection rates of mutant virus in antiviral treatment naïve patients could be influenced by the mutant virus prevalence in the society [7, 8]. Where there is no available data for HBV mutation rates, the mutation rates in the chronic HBV patients visiting hospital might be utilized to postulate the infection rates of mutant virus in antiviral treatment naïve patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [7] reported the rate of natural YMDD mutations in Western China as 15.56% from 270 antiviral non-treated (treatment naïve) chronic hepatitis B patients. Moreover, Tan et al [8] found natural YMDD mutations in 23.3% of 1,042 patients recruited from six centers in China. They posited that the natural existence of YMDD mutant strains was associated with a larger HBV load in chronic hepatitis B patients.…”
Section: Introductionmentioning
confidence: 99%
“…180. kodonda oluşan L180M/C mutasyonunun ise tek başına direnç oluşumunda yeterli olmadığı, ancak rtM204V/I/S ile birlikte bulunduğunda hem replikasyonu hem de LVD direncini artırdığı gösterilmiştir 8 . Yapılan çalışmalarda YVDD mutasyonuna hemen daima L180M mutasyonunun eşlik ettiği, YIDD tipi mutasyonların ise tek başına da görülebileceği bildirilmektedir [10][11][12] . Çalışmamızda da dizi analizi ile YVDD mutasyonu bir örnekte L180M ve S202G mutasyonları ile bir arada bulunmuştur.…”
Section: Discussionunclassified
“…The most common combination mutations include amino acid changes at rt180 + rt204, rt181 + rt236 and rt173 + rt180 + rt204 [63]. The methionine at rt204 is part of the YMDD active site in box C; the rt173, rt180 and rt181 positions are in box B; and rt236 is in box D. In addition to these most common mutations, several mutations have been associated with NRTI treatment [60,6468].…”
Section: Importance Of Different Domains Motifs and Residuesmentioning
confidence: 99%